Arts councils, policy-making and "the local". Issue 4 (8th August 2019) - Durrer, Victoria; Gilmore, Abigail; Stevenson, David
ABSTRACT: In the British Isles, national policies for the arts are primarily viewed as the responsibility of arts councils with statutory duties to distribute state funding that meet the requirements of both "arms-length" principles and national strategic frameworks. This paper explores the tensions between policy making for the nation-state and for "the local" through comparative research on the arts councils (and equivalent bodies) in Scotland, England and Northern Ireland. Drawing on in-depth qualitative interviews with senior representatives from these organisations, it explores their notions of, responsibilities to and affiliations with "the local". Findings suggest that despite their different models and relationships to the nation-state, and the disparities in the scale of investment, these national policy bodies commonly rely on networked governance to facilitate their relationship to "the local" which risks reproducing national interests, limiting the localised agency of place-based approaches and contributing to a culture of competition within cultural policy.